Daily risk of adverse outcomes in patients undergoing complex lesions revascularization: A subgroup analysis from the RAIN-CARDIOGROUP VII study (veRy thin stents for patients with left mAIn or bifurcatioN in real life). (1st September 2019) - Biolè, Carloalberto; Huczek, Zenon; Nuñez-Gil, Ivan; Boccuzzi, Giacomo; Autelli, Michele; Montefusco, Antonio; Trabattoni, Daniela; Ryan, Nicola; Venuti, Giuseppe; Imori, Yoichi; Takano, Hitoshi; Matsuda, Junya; et al.
Abstract: Introduction: Percutaneous coronary intervention (PCI) for complex lesions, including unprotected left main (ULM) and bifurcations, is gaining a relevant role in treating coronary artery disease with good outcomes, also thanks to new generation stents. The daily risk of adverse cardiovascular events and their temporal distribution after these procedures is not known. Methods: All consecutive patients presenting with a critical lesion of ULM or bifurcation treated with very thin struts stents, enrolled in the RAIN-Cardiogroup VII study, were analyzed. The daily risk of major acute cardiovascular events (MACE), target lesion revascularization (TLR) and stent thrombosis (ST) and their temporal distribution in the first year of follow-up was the primary endpoint. Differences among subgroups (ULM, patient presentation, kind of stent polymer) were the secondary endpoint. Results: 2745 patients were included, mean age 68 ± 11 years, 33.3% diabetics, 54.5% had an acute coronary syndrome (ACS); 88.5% of treated lesions were bifurcations, 27.2% ULM. Average daily risk was 0.022% for MACE, 0.005% for TLR and 0.004% for ST, in the first year. Bimodal distribution of adverse events, especially TLR, with an early peak in the first 50 days and a late one after 150 days, was observed. Patients with ULM presented a significantly higher daily risk of events, and ACS patients presented higher MACE risk. No difference emerged according to the type of stent polymer. Conclusions: The daily risk of adverse events in the first year after complex PCI in our study is acceptably low. PCI on ULM carries a higher risk of complications. Highlights: PCI for complex lesions with new stents carries a low daily risk of adverse events. Daily risks are 0.022% for MACE, 0.005% for TLR and 0.004% for ST in the first year. Daily risks of TLR and ST show a bimodal distribution. PCI on ULM carries a higher risk of complications. Stent polymer is not associated with a difference in the daily risk of events.